(n-6)*4=40

Simple and best practice solution for (n-6)*4=40 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (n-6)*4=40 equation:


Simplifying
(n + -6) * 4 = 40

Reorder the terms:
(-6 + n) * 4 = 40

Reorder the terms for easier multiplication:
4(-6 + n) = 40
(-6 * 4 + n * 4) = 40
(-24 + 4n) = 40

Solving
-24 + 4n = 40

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '24' to each side of the equation.
-24 + 24 + 4n = 40 + 24

Combine like terms: -24 + 24 = 0
0 + 4n = 40 + 24
4n = 40 + 24

Combine like terms: 40 + 24 = 64
4n = 64

Divide each side by '4'.
n = 16

Simplifying
n = 16

See similar equations:

| -171x-9x=10x+19 | | 3x+x/2=15 | | 3a-4=0 | | 8x+3=x+38 | | x*2=8 | | 4x*5x=20 | | 4x+3x=12 | | 4x+5x=200 | | 4x+5x=10 | | 4x+5x=100 | | 4yx+5x=20 | | 4x+5y=5y | | b-8=10 | | 5x+4y=31 | | a-8=4 | | 2y-15+3y+3=24 | | z-5=r | | a+9=16 | | 2s+4t-2s-3t= | | 8z=-104 | | 5x=-65 | | 74-6x=12x+18 | | 13-9x=57-23x | | 83-3x=24x+17 | | 5-10x=170-45x | | 62-6x=8x-4x | | 132-5x=4x+24 | | -17-6x=7-10x | | 119-6x=10x+63 | | 4x+29=6x+11 | | 3x+5x=5+x | | 2p+3=4+5p |

Equations solver categories